Increased equality of opportunity through international tourism. Issue 4 (23rd October 2019) - Hipsher, Scott
Abstract : Purpose: The purpose of this study is to explore and compare the perceptions of workers in the tourism industry in Thailand in foreign-owned and locally owned firms to provide an underrepresented perspective in the debate over whether international trade and tourism primarily exploits workers or provides valuable opportunities. Design/methodology/approach: A matched-pairs comparative analysis was used. Findings: Workers at foreign-owned companies showed slightly, although statistically insignificant, more positive attitudes toward tourism as a means of creating opportunities for themselves. Workers in foreign-owned companies showed a statistically significant more positive attitude toward the impact of tourism on the country. It appears the vast majority of the workers interviewed did not feel exploited, but empowered by opportunities to engage in employment in the tourism industry. Research limitations/implications: The use of self-reported measures has been acknowledged to be problematic and the size and composition of the sample limit the ability to generalize the findings to a broader population. Practical implications: Understanding the perspectives of the workers in an industry can be useful in policy development and implementing corporate social responsibility programs. The results suggest workers would support programs which encourage increases in tourism and foreign investment in the industry. Social implications reflect the perceptions of an under-represented segment of society. Originality/value: The intention is to help bring into the debate the perspectives of individuals who are most directly affected by these activities.